2016
DOI: 10.18869/acadpub.rmm.4.4.38
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cytochrome P450 2 C9 and Vitamin K Epoxide Reductase Complex Subunit 1 Polymorphisms with Warfarin dose among Iranian Patients

Abstract: Background: Warfarin is a common anticoagulant drug that has a narrow therapeutic index; higher dose causes excessive bleeding and lower dose leads to cerebrovascular clotting and stroke in patients. Genetic factors that have been associated with warfarin response are the genes of cytochrome P450 2C9 (CYP2C9), which metabolize the more active S-enantiomer of warfarin, and vitamin K epoxide reductase (VKOR), the target site for warfarin. The present study was conducted to investigate the association between CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In contrast to Kermanshah population, most of the subjects in Birjand showed more variant allele frequency of CYP2C9*2 , CYP2C9*3 , and VKORC1-1639 G>A as 9.1, 10, and 31.9%, respectively( 29 ). Furthermore, Dalily and Ramazani in 2012( 30 ) and Kameli, et al . in 2016( 31 ) in two separate studies in Iran reported different genotype frequencies for CYP2C9*2 , CYP2C9*3 and/or VKORC1 compared to the obtained results in our study ( Table 5 ).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to Kermanshah population, most of the subjects in Birjand showed more variant allele frequency of CYP2C9*2 , CYP2C9*3 , and VKORC1-1639 G>A as 9.1, 10, and 31.9%, respectively( 29 ). Furthermore, Dalily and Ramazani in 2012( 30 ) and Kameli, et al . in 2016( 31 ) in two separate studies in Iran reported different genotype frequencies for CYP2C9*2 , CYP2C9*3 and/or VKORC1 compared to the obtained results in our study ( Table 5 ).…”
Section: Discussionmentioning
confidence: 98%